Analysis of the epidemiological profile of overweight and hypertensive adolescents in the state of Sergipe (Research, Society and Development, 2021)
Introduction: Systemic arterial hypertension (SAH) associated with overweight and obesity is a very common condition in the world, its prevalence is increasing in children and adolescents, being responsible for a great impact on quality of life, with direct interference in the growth and development of individuals. In Brazil, the prevalence of systemic arterial hypertension in the pediatric population ranges from 1% to 13% and about 20% of Brazilian adolescents are overweight. Systemic arterial hypertension in childhood has been associated with a recent obesity epidemic, children and adolescents with high blood pressure levels are more likely to become adults with systemic arterial hypertension, which is associated with events such as stroke, acute myocardial infarction, heart failure, peripheral arterial disease and chronic kidney disease. Justification: There is an important gap in the existing information on this topic in the state of Sergipe, thus enabling the construction of this research project. Objective: To analyze the epidemiological profile and the association between obesity and hypertension in adolescents in the state of Sergipe. Methods: Descriptive epidemiological study of secondary data, quantitative, documentary, cross-sectional, exploratory, retrospective, health assessment approach whose data were collected in the registration and monitoring system for hypertensive and diabetic patients (HIPERDIA) - DATASUS-MS, referring to individuals diagnosed with systemic arterial hypertension in Sergipe from 2002 to 2013.